Productivity and nutritive value of elephant grass (cv. BRS Capiaçu) at different cutting ages after planting (Bioagro, 2025)
Due to their high dry matter production and balanced nutritive value per unit area, Elephant grass cultivars are excellent for bulky supplementation during the dry season. The objective was to evaluate the productivity and nutritive value of the BRS Capiaçu cultivar through different cutting ages after planting. The experimental design was conducted in completely randomized blocks, with four cutting ages: 60, 90, 120, and 150 days, each with five replications (blocks), totaling 20 experimental units, covering a total area of 12 m². As age advanced, linear increases in productivity were observed (p≤0.01), reaching an average height of 4.60 m, a green matter productivity of 252.60 t·ha-1, and a dry matter productivity of 67.36 t·ha-1 at 150 days after planting. Regarding nutritional value, linear increments (p≤0.01) were found in dry matter, organic matter, and neutral detergent fiber levels, while mineral matter and crude protein exhibited a linear reduction (p≤0.01). However, no effects (p>0.17) were observed with advancing cutting age after planting for acid detergent fiber, and hemicellulose variables. It is concluded that increasing the cutting age reduces the forage's nutritional value. From this perspective, the 90-day age proved to be more suitable for cutting BRS Capiaçu elephant grass.
Keywords: Biomass production; Cenchrus purpureus; harvesting times